ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI EKSPOR PERHIASAN INDONESIA KE SINGAPURA 2003 - 2018 - Aziz Dimas Muhammad; Syapsan Syapsan; Darmayuda Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Singapore's GDP, the exchange rate, and gold prices affecting the value of Indonesian jewelry exports to Singapore in 2003 - 2018. This study uses secondary data obtained from data from the Central Statistics Agency (BPS), World Bank and Bank Indonesia. The analytical method used is Multiple Linear Regression Analysis with the Ordinary Least Square (OLS) least squares analysis, testing of hypotheses and data suitability (classical assumptions) using a 5% significance level. Based on the results of the study it is known that simultaneously Singapore's GDP, the exchange rate,and gold prices affecting the value of Indonesian jewelry exports to Singapore. However, partially, Singapore's GDP has a positive and significant effect on the value of Indonesian jewelry exports to Singapore, the exchange rate is obtained partially and does not have a significant negative effect on the value of Indonesian jewelry exports to Singapore, and gold prices partially has a negative and significant effect on the value of Indonesian jewelry exports to Singapore.Keywords: GDP, Exchange Rate, Gold Prices, and Jewelry Export